Does social media promote democracy? Some empirical evidence - Chandan Kumar Jha; Oasis Kodila-Tedika (African Governance and Development Institute (AGDI), 2019)
This study explores the relationship between social media and democracy in a cross- section of over 125 countries around the world. We find the evidence of a strong, positive correlation between Facebook penetration (a proxy for social media) and democracy. We further show that the correlation between social media and democracy is stronger for low-income countries than highincome countries. Our lowest point estimates indicate that a one-standard deviation (about 18 percentage point) increase in Facebook penetration is associated with about 8-point (on a scale of 0-100) increase for the world sample and over 11 points improvement for low-income countries.
Keywords: D72; D83; O1; 330; Democracy; Information; Facebook; Internet; Social Media